(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
This work assessed the physicochemical characteristics of aquaculture effluents generated in aquaculture farms in Kano State to establish their suitability as irrigation water. Samples were collected from different aquaculture farms in the urban and peri-urban areas where the farms are clustered, and the physicochemical parameters, including the concentrations of nutrients, heavy metals, electrical conductivity (EC), and sodium adsorption ratio (SAR) were evaluated. The physicochemical characteristics of the effluents vary across the farms and the differences in the mean values were statistically significant at the 0.05 confidence interval. However, post hoc analysis based on the Fisher LSD test showed that the concentrations of certain individual parameters were not statistically different at the 0.05 interval. The concentrations of heavy metals were mostly within the standard limits. The EC values of the samples ranged from 0.85 dS/m to 2.4 dS/m, which are classified as having ‘slight to moderate restriction’ based on the FAO guidelines. Based on the combined EC and SAR analysis, some effluents fall under the “none” degree of restriction and are, therefore, suitable for irrigation. However, for some samples, such as that obtained from Farm No. 8 with SAR of 4.48 and a corresponding EC of 104 dS/m, the effluents are classified as having “slight to moderate” degrees of restriction, and should therefore be used with caution. The results show that although aquaculture effluents can be used as irrigation water, high SAR and EC may pose challenges. Thus, it is necessary to evaluate the suitability of the effluents before using them